Development of haemostatic decontaminants for the treatment of wounds contaminated with chemical warfare agents. 2: Evaluation of in vitro topical decontamination efficacy using undamaged skin1. Issue 5 (12th September 2014) - Dalton, Christopher H.; Hall, Charlotte A.; Lydon, Helen L.; Chipman, J. K.; Graham, John S.; Jenner, John; Chilcott, Robert P.
Abstract: The risk of penetrating, traumatic injury occurring in a chemically contaminated environment cannot be discounted. Should a traumatic injury be contaminated with a chemical warfare (CW) agent, it is likely that standard haemostatic treatment options would be complicated by the need to decontaminate the wound milieu. Thus, there is a need to develop haemostatic products that can simultaneously arrest haemorrhage and decontaminate CW agents. The purpose of this study was to evaluate a number of candidate haemostats for efficacy as skin decontaminants against three CW agents (soman, VX and sulphur mustard) using an in vitro diffusion cell containing undamaged pig skin. One haemostatic product (WoundStat™) was shown to be as effective as the standard military decontaminants Fuller's earth and M291 for the decontamination of all three CW agents. The most effective haemostatic agents were powder‐based and use fluid absorption as a mechanism of action to sequester CW agent (akin to the decontaminant Fuller's earth). The envisaged use of haemostatic decontaminants would be to decontaminate from within wounds and from damaged skin. Therefore, WoundStat™ should be subject to further evaluation using an in vitro model of damaged skin. Copyright © 2014 Crown copyright. Journal of Applied Toxicology © 2014 John Wiley & Sons, Ltd. Abstract : There is a need to develop haemostatic products that can simultaneously arrest haemorrhage and decontaminate CW agents from within wounds. The purpose of this study was to evaluate a number of candidate haemostats for efficacy as skin decontaminants against three CW agents (soman, VX and sulphur mustard) using an in vitro diffusion cell containing undamaged pig skin. Two products were shown to be effective and will be subject to further assessment using damaged skin.